IMPROVING SELF-GOVERNANCE IN THE LEGAL PROFESSION OF UZBEKISTAN: PROBLEMS, TRANSFORMATION, AND PROSPECTS - Zokirova , Diyora (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis examines the issues of improving self-governance mechanisms within the legal profession of Uzbekistan. Based on international standards, particularly those developed by the United Nations, as well as European practices, the current state of the national system is analyzed. Key aspects such as the independence of the legal profession, professional ethics, internal governance mechanisms, and digitalization processes are explored. The study identifies institutional constraints, insufficient internal control mechanisms, and underdeveloped professional standards as major challenges. The research proposes scientifically grounded recommendations aimed at transforming the legal profession in line with international standards.